Identifying the Components of Teaching Digital Media Literacy in Primary Schools - Farahani, Masoumeh; Hallaj Dehghani, Adel; Khanzadi, Khadijeh (Iranian Journal of Educational Sociology, 2022)
Purpose: In the context of rapidly evolving digital landscapes, digital media literacy has become a foundational element in primary education, crucial for preparing students to navigate and influence their digital surroundings effectively. This study aims to identify and describe the key components of digital media literacy as taught in primary schools, focusing on the insights of faculty members from Iran to understand how these components are integrated into the educational system.Methodology: Employing a qualitative research design, this study gathered data through semi-structured interviews with 21 faculty members who are directly involved in teaching digital media literacy in primary schools across Iran. Theoretical saturation was achieved to ensure comprehensive coverage of the concepts. Data were analyzed using NVivo software to facilitate a thorough thematic analysis, identifying the core components of digital media literacy education.Findings: The analysis revealed five main themes central to digital media literacy in primary education: Transfer, Usage, and Digital Competence; Computer Fundamentals; Online Basics Skills; Word Processing, Spreadsheet, and Presentation Skills; and Database and Data Security Skills. Each theme comprised several categories that detailed specific skills and knowledge areas essential for comprehensive digital literacy, ranging from basic computer operations to advanced data management and security.Conclusion: The study underscores the importance of a robust digital media literacy curriculum in primary education, highlighting specific skills that are crucial for students' development as competent digital citizens. It also points to the need for ongoing teacher training to keep pace with technological advancements, ensuring that educators are well-equipped to impart these essential skills.